Decrease in IL‐10 and increase in TNF‐α levels in renal tissues during systemic inhibition of nitric oxide in anesthetized mice. Issue 2 (10th February 2014) - Singh, Purnima; Castillo, Alexander; Majid, Dewan S. A.
Abstract Earlier, we demonstrated that the inhibition of nitric oxide synthase (NOS) by nitro‐l‐arginine methyl ester (l‐NAME) infusion increases the endogenous production of proinflammatory cytokine, tumor necrosis factor (TNF‐α). In the present study, we examined the hypothesis that inhibition of nitric oxide (NO) production leads to the suppression of interleukin (IL)‐10 (anti‐inflammatory cytokine) generation which facilitates the enhancement of TNF‐α production endogenously. Using appropriate enzyme‐linked immunosorbent assay kits and immunohistochemical staining, the levels of IL‐10 and TNF‐α in plasma (P) and in renal tissues (R) were measured in anesthetized mice (C57BL/6; ~10 weeks age; n = 6/group) infused with or without l‐NAME (200 μg/min/kg; i.v. for 2 h). Compared to vehicle‐treated control mice, l‐NAME‐treated mice had a lower level of IL‐10 (P, 0.3 ± 0.1 vs. 2.6 ± 0.6 ng/mL; R, 0.5 ± 0.1 vs. 3 ± 0.1 ng/mg protein) and a higher level of TNF‐α (P, 432 ± 82 vs. undetected pg/mL; R, 58 ± 7 vs. 6 ± 5 pg/mg protein). IL‐10 protein expression, present mostly in the distal nephron segments in control mice, was markedly downregulated in l‐NAME‐treated mice. Compared to control mice, TNF‐α expression increased 2.5‐fold in renal cortical sections (mostly in the distal nephron segments) in l‐NAME‐treated mice. Coinfusion of a NO donor, S‐nitroso‐N‐acetyl‐penicillamine (SNAP; 25 μg/min/kg) with l‐NAME in a separate group of mice prevented these changes in IL‐10 and TNF‐α induced by l‐NAME. IL‐10 infusion (0.075 ng/min/g) in l‐NAME‐treated mice markedly attenuated l‐NAME‐induced increments in TNF‐α. Thus, these results demonstrate that NOS inhibition decreases endogenous IL‐10 generation and thus, minimizes its immune downregulating action on the TNF‐α production in the kidney.